Beyond Imagination: Deleuze and the Real Virtual - Capodivacca, Silvia (Aesthetica Preprint, 2023)
During three years, from 1963 to 1966, Deleuze published three texts dedicated, respectively, to Kant, Proust and Bergson. In the last two, the most important concept that emerges is undoubtedly that of virtual, whereas in the volume on the critical philosophy of Kant the author speaks instead of imagination. If the latter is connoted as the faculty that prolongs, multiplying them, the possibilities of reality and of the ego that overlooks it and if, on the other hand, the virtual is the being that goes beyond its own current determination and that makes its differences proliferate, it is legitimate to ask how much these two notions have in common. The paper is therefore devoted to the definition of these two concepts, to verify whether and to what extent they coincide. In fact, it would seem that for Deleuze, the virtual is what brings to ontological completion the work of the imagination, desubjectifying its character and thus allowing the crossing of the gnoseological field within which it was convened.